(untitled) (Psychology Travelogs, 2024)
The article is devoted to the problem of stress resistance of the individual in the conditions of modern society, characterized by a high level of social tension and psychological pressure. The purpose of the article is a theoretical review of the concept of stress resistance, psychodiagnostic methods for studying stress resistance and integrative models of its development. The paper reviews the theoretical frameworks of stress and coping mechanisms, starting from Hans Selye’s foundational concept of stress as a universal response to external factors to modern interpretations focusing on subjective perceptions and adaptive strategies. An analysis of the phenomenon of stress resistance was carried out, its key components and formation factors were identified. The main methods for assessing coping strategies (strategies for overcoming stress) are described, as well as integrative models of adaptation, such as BASIC Ph, which allow studying the mechanisms of stress resistance development. Particular attention is paid to the role of emotional intelligence, positive self-esteem and cognitive resources in strengthening the adaptive capabilities of the individual. It is concluded that stress resistance is a multidimensional psychological phenomenon that is formed due to both internal and external resources of the individual. Stress resistance includes the ability to self-regulate and effectively overcome stress using adaptive strategies. The development of emotional intelligence, positive self-esteem and cognitive adaptation strategies contribute to the increase in stress resistance. Test methods for assessing coping strategies and adaptation models, such as BASIC Ph, allow for a deeper understanding of the mechanisms that contribute to stress resilience and find practical tools for its development.